Cultural Differences, Assimilation and Behavior: Player Nationality and Penalties in Football - Giacomo De Luca; Jeroen Schokkaert; Johan F. M. Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2011)
We examine the impact of a different cultural background on individual behavior, focusing on violence on the football field of southern European and nothern European football players in the English Premier League. We find that southern European football players collect on average more football penalties than their nothern European colleagues. We also find that the initially higher number of football penalties incurred by southern European players converges towards the local average, the longer their experience in the Premier League.
Keywords: J61; L83; Z10; 330; Football; Violent Behavior; Culture; Assimilation